Ninth Five Year Plan 1997-2002 Volume I - Planning Commission, Government of India (Planning Commission, Government of India, 1997)
The Ninth Five Year Plan, launched in the 50th year of India’s Independence, will take the country into the new millennium. Much has happened in the fifty years since independence. The people of India have conclusively demonstrated their ability to forge a nation united despite its diversity, and their commitment to pursue development within the framework of a functioning, vibrant and highly pluralistic democracy. In this process democratic institutions have put down firm roots and flourished and development has also taken place on a wide front. As the millennium draws to a close, the time has come to redouble our efforts at development, especially in the social and economic spheres, so that the country will realise its full economic potential and the poorest and the weakest will be able to shape their destiny in an unfettered manner. This will require not only higher rates of growth of output and employment, but also a special emphasis on allround human development, with stress on social sectors and a thrust on eradication of poverty.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Ninth Five Year Plan- India